Clinical tools used in young infants born very preterm to predict motor and cognitive delay (not cerebral palsy): a systematic review. (13th November 2020) - Caesar, Rebecca; Colditz, Paul B; Cioni, Giovanni; Boyd, Roslyn N
Abstract : Aim: This systematic review evaluates the accuracy of clinical tools used at a corrected age of 6 months or younger to predict motor and cognitive delay (not cerebral palsy) at 24 months' corrected age, in infants born very preterm. Method: Six databases were searched. Quality was evaluated using the Quality Assessment of Diagnostic Accuracy Studies tool. Predictive analysis included calculation of sensitivity and specificity, inspection of summary receiver operating characteristics curves, and bivariate meta‐analysis. Results: Six assessments were identified in 10 studies of 992 infants. Overall prevalence of motor delay was 13.8% and cognitive delay was 11.7%. Methodological quality was variable for patient selection, reference standard, flow, and timing. All studies had a low risk of bias for the index test. General Movement Assessment (GMA) predicted motor and cognitive outcomes with good accuracy for mild, moderate, and severe delays (fidgety age: pooled diagnostic odds ratio=12.3 [5.9–29.8]; hierarchical summary receiver operating characteristics curve=0.733). The Hammersmith Infant Neurological Examination (HINE) demonstrated excellent predictive accuracy for severe motor delay (3mo and 6mo; sensitivity 93% [68–100%], specificity 100% [96–100%]) but showed limited ability to predict milder delays. Interpretation: In the population of infants born very preterm, few assessment tools used at 6 months or younger corrected age have proven predictive accuracy for cognitive and motor delay at 24 months' corrected age. Only the GMA and HINE demonstrated useful predictive validity. What this paper adds: General movements have predictive validity for both motor and cognitive dysfunction in infants born very preterm. The Hammersmith Infant Neurological Examination showed the highest predictive accuracy for severe motor delay. The General Movement Assessment was the best tool to predict mild‐to‐moderate motor and cognitive delays. What this paper adds: General movements have predictive validity for both motor and cognitive dysfunction in infants born very preterm. The Hammersmith Infant Neurological Examination showed the highest predictive accuracy for severe motor delay. The General Movement Assessment was the best tool to predict mild‐to‐moderate motor and cognitive delays. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Herramientas clínicas utilizadas en lactantes nacidos muy prematuros para predecir el retraso motor y cognitivo (no la parálisis cerebral): una revisión sistemática: Objetivo: Esta revisión sistemática evalúa la precisión de las herramientas clínicas utilizadas a una edad corregida de 6 meses o menos para predecir el retraso motor y cognitivo (no la parálisis cerebral) a los 24 meses de edad corregida, en bebés nacidos muy prematuros. Método: Se realizaron búsquedas en seis bases de datos. La calidad se evaluó mediante la herramienta Evaluación de la calidad de los estudios de precisión diagnóstica. El análisis predictivo incluyó el cálculo de la sensibilidad y la especificidad, la inspección de las curvas de resumen de las características operativas del receptor y el metanálisis bivariado. Resultados: Se identificaron seis evaluaciones en 10 estudios de 992 lactantes. La prevalencia global de retraso motor fue del 13, 8% y el retraso cognitivo fue del 11, 7%. La calidad metodológica fue variable para la selección de pacientes, estándar de referencia, flujo y tiempo. Todos los estudios tuvieron un bajo riesgo de sesgo para la prueba índice. La Evaluación de los Movimientos Generales (GMA) predijo resultados motores y cognitivos con buena precisión para retrasos leves, moderados y graves (edad movimientos inquietos: razón de posibilidades diagnósticas agrupadas = 12, 3 [5, 9‐29, 8]; curva de características operativas resumidas jerárquicas del receptor = 0, 733). El examen neurológico infantil de Hammersmith (HINE) demostró una precisión predictiva excelente para retrasos motores graves (3 meses y 6 meses; sensibilidad 93% [68‐100%], especificidad 100% [96‐100%]) pero mostró una capacidad limitada para predecir retrasos más leves. Interpretación: En la población de bebés nacidos muy prematuros, pocas herramientas de evaluación utilizadas a los 6 meses o antes de la edad corregida han demostrado una precisión predictiva para el retraso cognitivo y motor a los 24 meses de edad corregida. Solo la GMA y HINE demostraron una validez predictiva útil. Instrumentos clínicos usados em crianças pequenas nascidas muito prematuras para predizer o atraso motor e cognitivo (não paralisia cerebral): uma revisão sistemática: Objetivo: Esta revisão sistemática avaliou a acurácia de ferramentas clínicas usadas na idade corrigida de 6 anos ou menos para predizer atraso motor e cognitivo (não paralisia cerebral) aos 24 meses de idade corrigida, em lactentes nascidos muito prematuros. Método: Seis bases de dados foram pesquisadas. A qualidade foi avaliada usando a ferramenta Avaliação de qualidade de Estudos de Acurácia Diagnóstica. Análise preditiva incluiu o cálculo da sensibilidade e especificidade, inspeção da síntese das curvas to tipo "receiver operating" características, e metanálise bivariada. Resultados: Seis avaliações foram identificadas em 10 estudos com 992 lactentes. A prevalência geral de atraso motor foi 13, 8% e atraso cognitivo foi 11, 7%. A qualidade metodológica foi variável para a seleção de pacientes, padrão de referência, fluxo e tempo. Todos os estudos tiveram baixo risco de viés. A General Movement Assessment (GMA) foi preditiva de resultados motores e cognitivos com boa acurácia para atrasos leves, moderados e severos (idade de fidgety: taxa de risco diagnóstico agrupado =12, 3 [5, 9–29, 8]; síntese hierárquica da curva receiver operating característica =0, 733). O Exame neurológico infantil de Hammersmith (HINE) demonstrou excelente acurácia preditiva para atraso motor severo (3m e 6m; sensibilidade 93% [68–100%], especificidade 100% [96–100%]) mas mostrou capacidade limitada de predizer atrasos mais leves. Interpretação: Na população de lactentes nascidos muito prematuros, poucos instrumentos de avaliação usados na idade de 6 meses de idade corrigida ou menos mostraram acurácia preditiva comprovada para atraso motor e cognitivo aos 24 meses de idade corrigida. Apenas a GMA e HINE demonstraram validade preditiva útil.